2007
DOI: 10.1098/rspb.2007.0417
|View full text |Cite
|
Sign up to set email alerts
|

The scaling of leaf area and mass: the cost of light interception increases with leaf size

Abstract: For leaves, the light-capturing surface area per unit dry mass investment (specific leaf area, SLA) is a key trait from physiological, ecological and biophysical perspectives. To address whether SLA declines with leaf size, as hypothesized due to increasing costs of support in larger leaves, we compiled data on intraspecific variation in leaf dry mass (LM) and leaf surface area (LA) for 6334 leaves of 157 species. We used the power function LM=alpha LAbeta to test whether, within each species, large leaves dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
230
4
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(264 citation statements)
references
References 32 publications
26
230
4
4
Order By: Relevance
“…We assessed leaf quality by using the mean SLA, which is the ratio of leaf area (cm 2 ) to leaf dry mass (g). SLA is a key ecological and physiological plant trait [44] that often correlates with leaf toughness, nutrient concentration and breakdown rate [45,46]. To measure SLA, we scanned 20 leaves of each plant species, estimated their areas with IMAGEJ 10.2, dried them to constant mass and weighed them to the nearest 0.1 mg. We then calculated the mean SLA at each site.…”
Section: (B) Climatic and Leaf Quality Datamentioning
confidence: 99%
“…We assessed leaf quality by using the mean SLA, which is the ratio of leaf area (cm 2 ) to leaf dry mass (g). SLA is a key ecological and physiological plant trait [44] that often correlates with leaf toughness, nutrient concentration and breakdown rate [45,46]. To measure SLA, we scanned 20 leaves of each plant species, estimated their areas with IMAGEJ 10.2, dried them to constant mass and weighed them to the nearest 0.1 mg. We then calculated the mean SLA at each site.…”
Section: (B) Climatic and Leaf Quality Datamentioning
confidence: 99%
“…This literature indicates that leaf size tends to decline with increasing elevation (Givnish 1984;McDonald et al 2003), decreasing mean annual temperature (Givnish 1984;McDonald et al 2003;Wolfe 1995), decreasing mean annual rainfall (Givnish 1984;McDonald et al 2003;Wolfe 1995), and decreasing soil fertility (McDonald et al 2003). Leaf size can also vary across several orders of magnitude within individual plant communities (Givnish 1984;Milla and Reich 2007;Li et al 2008). …”
Section: Introductionmentioning
confidence: 99%
“…Although scaling relationships are common in the biological world and have been extensively studied [32][33][34][35][36][37][38], only scant attention has been paid to the scaling of GS with other plant traits. In an early study, Baetcke et al [39] found that the slope of the interspecific relationship between GS and nuclear volume is approximately 1 (i.e.…”
Section: Introductionmentioning
confidence: 99%